In vivo micro-CT imaging of untreated and irradiated orthotopic glioblastoma xenografts in mice: capabilities, limitations and a comparison with bioluminescence imaging - Kirschner, Stefanie; Hartmann, Linda; Bierbaum, Miriam; Maros, Máté E.; Kerl, Hans Ulrich; Wenz, Frederik; Glatting, Gerhard; Giordano, Frank Anton (Journal of neuro-oncology, 2015)
Small animal imaging is of increasing relevance in biomedical research. Studies systematically assessing the diagnostic accuracy of contrast-enhanced in vivo micro-CT of orthotopic glioma xenografts in mice do not exist. NOD/SCID/γc−/− mice (n = 27) underwent intracerebral implantation of 2.5 × 106 GFP-Luciferase-transduced U87MG cells. Mice underwent bioluminescence imaging (BLI) to detect tumor growth and afterwards repeated contrast-enhanced (300 µl Iomeprol i.v.) micro-CT imaging (80 kV, 75 µAs, 360° rotation, 1,000 projections, 33 s scan time, resolution 40 × 40 × 53 µm, 0.5 Gy/scan). Presence of tumors, tumor diameter and tumor volume in micro-CT were rated by two independent readers. Results were compared with histological analyses. Six mice with tumors confirmed by micro-CT received fractionated irradiation (3 × 5 Gy every other day) using the micro-CT (5 mm pencil beam geometry). Repeated micro-CT scans were tolerated well. Tumor engraftment rate was 74 % (n = 20). In micro-CT, mean tumor volume was 30 ± 33 mm3, and the smallest detectable tumor measured 360 × 620 µm. The inter-rater agreement (n = 51 micro-CT scans) for the item tumor yes/no was excellent (Spearman-Rho = 0.862, p < 0.001). Sensitivity and specificity of micro-CT were 0.95 and 0.71, respectively (PPV = 0.91, NPV = 0.83). BLI on day 21 after tumor implantation had a sensitivity and specificity of 0.90 and 1.0, respectively (PPV = 1.0, NPV = 0.5). Maximum tumor diameter and volume in micro-CT and histology correlated excellently (tumor diameter: 0.929, p < 0.001; tumor volume: 0.969, p < 0.001, n = 17). Irradiated animals showed a large central tumor necrosis. Longitudinal contrast enhanced micro-CT imaging of brain tumor growth in live mice is feasible at high sensitivity levels and with excellent inter-rater agreement and allows visualization of radiation effects.
Gesehen am 15.11.2017